Pendekatan Konseling Islam terhadap Anomie dan Solidaritas Religius Tinjauan Teori Bunuh Diri Durkheim dalam Konteks Islam Borneo - Tiara (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
Suicide is a social phenomenon that continues to draw global concern, including in Indonesia. Although Islam strictly prohibits suicide, such cases still occur among Muslim communities, including in Borneo. This article analyzes the phenomenon of suicide in Islamic Bornean society through Emile Durkheim’s theory, which views suicide as a social symptom influenced by the levels of integration and regulation within a society. The study employs a library research method by reviewing classical sociological works, Bornean anthropological studies, and Islamic counseling literature, along with an analysis of reported suicide cases in the region. The findings indicate that suicide in Borneo primarily falls under the egoistic and anomic types, where the weakening of social solidarity and the pressures of modernization contribute to the risk of self-destruction. Meanwhile, Islamic and customary values function as protective factors but can also transform into social pressures through rigid norms and stigmatization. Through Islamic counseling, spiritual and social values can be integrated to reinforce moral regulation and provide psychological and religious support for individuals. Therefore, integrating Durkheim’s theory with Islamic counseling offers a comprehensive framework for understanding and preventing suicide in Islamic Bornean communities